Nutrient Leaching in Soil Affected by Fertilizer Application and Frozen Ground - Grant, K.N. (2020)
This study explored interactions between nutrient supply and infiltrating water during a simulated nongrowing season using a laboratory experiment to understand how water and nutrients move through partially frozen and unfrozen soil and if fertilizer placement influences NO3− and dissolved reactive P (DRP) leaching. Intact silt loam and clay soil monoliths (28 by 30 by 30 cm) were fertilized with P and N via subsurface placement or surface broadcast and subjected to simulated rainfall under unfrozen (10°C) and partially frozen (∼0°C) conditions. Conservative tracers (Br−, Cl−, and D2O) applied to characterize subsurface flow paths throughout a subset of events indicated that matrix flow dominated in unfrozen silt loam soil. However, preferential flow paths dominated in unfrozen clay and in both soil types under partially frozen conditions, transporting applied nutrients while minimizing contact with the soil matrix. The subsurface placement of inorganic fertilizer relative to surface broadcast reduced both NO3− (by 26.85 kg ha−1 [23%] in silt loam and 65.73 kg ha−1 [61%] in clay) and DRP losses (by 2.33 kg ha−1 [60%] in silt loam and 4.25 kg ha−1 [64%] in clay). This study demonstrates the advantage of subsurface placement of fertilizer in the reduction of nutrient leaching by limiting the interaction of the nutrient supply with preferential flow pathways.